Meaning of Symbols in the Beterang Ritual (Ka'aik Nari) Pada The Serawai Tribe Community, South Bengkulu Regency - Andre Andre; Yanto Yanto; Bayu Bayu (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2023)
The Beterang ritual ceremony (Ka'aik Nari) is the original culture of Serawai tribe, South Bengkulu Regency. The tribe is an indigenous people in Bengkulu Province. They perform the Beterang ritual ceremony (Ka'aik Nari) for the girls who are starting to enter their teens or puberty, aged 6-12 years. The child who is in Ka'aik Narikan undergoes several traditional rituals including going to Aik and Nari so that it is named Ka'aik Nari. This study aims to determine the meaning of the symbol in the Beterang (Ka'aik Nari) ceremony for Serawai people, South Bengkulu Regency. The type of research used is Descriptive-Qualitative, where the research explains the Beterang (Ka'aik Nari) ritual ceremony. Data collection techniques used are observation, interviews, documentation. Based on the results of the research found the Meaning of Symbols in the Beterang Ceremony (Ka'aik Nari) for Girls of Serawai Tribe in South Bengkulu Regency, based on the results of the research it can be seen that there are many symbolic meanings contained in it, one of which is the Meaning and Symbol of Beterang (Ka'aik Nari) found in every series, conditions and completeness of the Beterang ceremony (Ka'aik Nari). This can be seen in the flowers used which have various meanings, each movement has a meaning such as holding hands means praying, wiping the face and holding the heels means cleaning, bathing means purifying. The message contained in the Beterang ceremony (Ka'aik Nari) is to purify a child and want to show or tell people by celebrating dancing together.